The Effect of PQRST and SGD Methods on Students’ Reading Comprehension at Dehasen University - Febrianti, Mariska (Universitas Mathla'ul Anwar Banten, 2018)
This research aims to compare the effectiveness of two methods, PQRST (Preview, Question, Read, State and Test) and SGD (Small Group Discussion). It was carried out at the second semester students of Penjaskesrek Department, Dehasen University. The design was a quasi-experiment. The sample consisted of two classes; one was taught by the PQRST method and another by the SGD method. The instrument was a reading test, which was tried-out; the reliability was 0.917 (very high). The result was as follows: at the pretest, there was no significant difference between both group on all aspects and at the post test, there were no significant difference between both groups on general comprehension, reading to learn from the text, and reading to integrate information. However, SGD was found to be more effective on finding general information while PQRST was found to be more effective on reading to skim and finding simple information.